A new method to analyse the effect of multifocal contact lenses on visual function. Issue 2 (April 2018) - Sanchez, I.; Ortiz-Toquero, S.; Blanco, M.; Martin, R.
Highlights: Multifocal contact lens designs may have got some limitations on wearers' visual function quality, inducing ghosting, halos, visual fluctuation. A neural adaptation is necessary for an optimal visual performance with multifocal contact lens. Using a yellow filter could increase the visual acuity and contrast sensitivity with multifocal contact lens. Abstract: Purpose: Presbyopic contact lens (CL) fittings produce simultaneous vision, providing different retinal images that reduce visual quality and wearers' satisfaction. The purpose of this study was to develop a new method to isolate the multifocality effect of different CL options to manage presbyopia, analysing the impact on binocular visual acuity (VA), stereopsis and contrast sensitivity (CS) and determining the effect of the use of a yellow filter (YF) on visual function. Methods: A prospective and double-masked randomized pilot study involving 20 healthy volunteers was conducted. Four multifocal CLs and monovision CLs without far prescription were fitted. All subjects wore their spectacles over the CLs to guarantee optimum VA at distance. Binocular VA, stereopsis and CS were assessed after 20 min of CL wear with or without a YF of 455 nm. Results: Binocular VA decreased with all multifocal CLs (P < 0.05), as did stereopsis (P < 0.01). All presbyopia correction reduced CS compared with spectacles (P < 0.05), except aspheric designs, at a frequency of 3 cycles/° (P > 0.06). Using the YF, visual function improved; better binocular VA was found with all multifocal CLs (statistically significant (P < 0.02) with both low-addition designs), and better CS was observed at most spatial frequencies (statistically significant (P < 0.02) at low frequencies with all CLs). Conclusions: This pilot study proposes a simple method to analyse the impact of multifocal CL wear on VA, stereopsis and CS while maintaining habitual spectacle correction to assess the patient's short-term opinion and help practitioners and patients make a decision during presbyopia correction with CL fitting.